Tick distribution and comparative analysis of bovine blood microbiome in two provinces of South Africa using 16S rRNA PacBio sequencing approach - Khoza, Bongekile L.; Byaruhanga, Charles; Makgabo, S. Marcus; Nyangiwe, Nkululeko; Mnisi, Themba; Nxumalo, Samukelo; Oosthuizen, Marinda C.; Mnisi, Zamantungwa T. H. (Frontiers in Tropical Diseases, 2024)
IntroductionTicks are obligate ectoparasites recognized worldwide as major vectors of several disease-causing pathogens and are good indicators of disease distribution and epidemiology. Recent years have seen a growing concern regarding emerging and re-emerging of economically important tick-borne pathogens of livestock and humans worldwide. The overall objective of the study was to give an insight into current tick distribution and associated bacterial pathogens that may pose a threat to cattle in the sampled study sites.MethodsA total of 150 cattle were randomly selected from three study sites, Harrismith and Phuthaditjhaba in Free State Province and Bergville in KwaZulu Natal Province, South Africa. Blood samples were collected from the cattle and DNA was subjected to the 16S rRNA gene microbiome sequencing on the circular consensus PacBio sequencing platform. Ticks were also collected from various predilection sites of the sampled animals.ResultsA total of eight tick species were identified and Rhipicephalus evertsi evertsi (79.4%) was the most abundant followed by R. appendiculatus (11.7%), R. afranicus (2.6%), R. simus (2.6%), Hyalomma rufipes (1.2%), R. decoloratus (1.0%), H. truncatum (0.7%) and R. microplus (0.7%). The bacterial microbiome sequence analysis revealed up to 16 phyla and 30 classes in the three study sites. Proteobacteria was the most dominant bacterial phyla with a relative abundance of 67.2% (Bergville), 73.8% (Harrismith) and 84.8% (Phuthaditjhaba), followed by Firmicutes at 9.6% (Phuthaditjhaba), 18.9% (Bergville) and 19.6% (Harrismith).Conclusion and perspectivesThe Chao 1 index estimator revealed significant differences in the α-diversity of microbial communities among three study sites. This study expands the knowledge on tick fauna and microbial communities in the three study sites.